EFEKTIVITAS STRATEGI PEMBELAJARAN DAN PENGALAMAN GERAK TERHADAP KREATIVITAS GERAK SISWA KELAS AWAL SEKOLAH DASAR - SUMANTRI, MOHAMAD SYARIF; YUNENGSIH, ENENG; -, HASANUDIN (Program Studi Magister Pendidikan Anak Usia Dini, 2017)
The objective of the research is to study the effect of learning strategy and movement experiences toward the movement creativity of early primary student. The research used 2 X 2 factorial design and was with n of 48 children who was selected by simple random sampling technique. The results of the research are: (1) there is a significant difference of the movement creativity between those who are given taught by Inductive learning strategy and deductive learning strategy in the process of movement creativity. The movement creativity of those who are given taught by inductive learning strategy is higher than those who are given taught by deductive learning strategy. (2) for student who have high a experiences movement, it was found that student movement creativity taught by inductive learning strategy is higher than deductive learning strategy. (3) for the student who have low experirnces movement, it was found that the children movement creativity taught by deductive learning strategy is not different than inductive learning strategy. (4) there is an influence of interaction between giving the learning strategy and experiences movement towards the early primary movement creativity. It can be concluded that learning strategy and experiences movement in the student creativity. Keywords: Learning strategy, experiences movement, movement creativity